Analisis Peran Serta Komite dalam Manajemen Mutu Pendidikan di SD Negeri Karangrejo dan SD Negeri Bener Yogyakarta - Dewi Andriyani; Maria Dominika Niron (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research aims to analyze the involvement of school committees in managing the quality of education in schools. This research approach is descriptive qualitative. Data was collected through in-depth interviews with school committee administrators. Data analysis was carried out qualitatively using the interactive data analysis model from Miles and Huberman. Research findings show that the role of school committees in managing the quality of education in schools is realized in 4 roles, namely the role of the advisor (advisory agency) which is always actively involved from the start, as well as supervision related to planning to provide various considerations regarding learning programs, budgets, employee criteria and facilities. through meetings or conferences with the school, supporting agencies help the school find other sources of funding if needed and are voluntary. Especially in raising school funds, the school committee helps proactively by entrusting sales in the canteen with profits earmarked for the needs of students in need, finding donors and providing non-obligatory contributions for parents of students to extend financial support to the school. the role of the controller (controlling agency) plays the role of the school committee carrying out periodic evaluations and comprehensive reporting of the entire school program including its funding., and the final role of the committee mediator is always active in meetings to hear and receive input information and reports from student parents, bridging communication between various parties involved in the school environment.